Novel surfactant-free microencapsulation of molten salt using TiO2 shell for high temperature thermal energy storage: Thermal performance and thermal reliability - Park, Seunghee; Jo, Byeongnam (Journal of Energy Storage, 2023)
High temperature thermal energy storage is important to determine the imbalance between power supply and demand in concentrating solar power. Recently, latent heat storage technique has received considerable attention for enhancing the storage density and ultimately reducing the size of the storage system. This study aims to develop a surfactant-free sol-gel based synthesis protocol for microencapsulating a molten salt (potassium nitrate, KNO3) with titanium dioxide (TiO2) that is thermally stable and robust and investigate the effects of the synthesis parameters on thermal performance and thermal reliability of the molten salt microcapsules. Solvent was observed to determine the sol-gel reaction speed (i.e., TiO2 shell formation speed). Acetone is most appropriate for attaining robust TiO2 shells against temperature changes. Additionally, the effects of catalyst and precursor were also investigated to determine their optimal amounts in terms of the robustness and sustainability of KNO3@TiO2 microcapsules. Morphological characteristics including core-shell structure and chemical composition of KNO3@TiO2 microcapsules were analyzed by scanning electron microscopy and Fourier transform infrared spectroscopy. Thermal performance of microcapsules was measured using differential scanning calorimetry in ranges of 250–390 °C. Remarkably high encapsulation ratio and encapsulation efficiency were measured up to 70.3 % and 69.3 %, respectively. To demonstrate outstanding thermal reliability of KNO3@TiO2 microcapsules, thermal performance of the microcapsules was investigated via DSC for wide range of ramping (heating/cooling) rates (5, 10, and 20 °C/min) and for 100 repeated thermal cycles. The optimal synthesis recipe was determined to obtain robust and sustainable KNO3@TiO2 microcapsules, and furthermore outstanding thermal performance and reliability were achieved at elevated temperature condition up to 400 °C.
Keywords: High temperature thermal energy storages; Latent heat storage; Microcapsules; Molten salt; Performance reliability; Power; Storage technique; Surfactant-free; Thermal Performance; Thermal reliability; High temperature thermal energy storage; Microencapsulation; Molten salt; Thermal reliability; Titanium dioxide